2023
DOI: 10.1002/adma.202301257
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Reprogramming of Vitamin B3 Metabolism as a Nanotherapeutic Strategy towards Chemoresistant Cancers

Abstract: Cancer‐associated fibroblasts (CAFs) promote cancer stem cell (CSC)‐mediated chemoresistance and immunosuppressive tumor microenvironment. However, direct depletion of CAFs may increase cancer invasiveness and metastasis. As a generalized strategy against chemoresistant cancers, Gemini‐like homotypic targeting nanoparticles (NPs) are designed for two‐pronged CAF transformation and cancer cell elimination. The CAF‐targeted NPs couple vitamin B3 metabolic reprogramming to epigenetic modulation of secreted pro‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…(C) Schematic depiction of a hydrogel platform for codelivery of CAFs and cancer cell-targeted nanoparticles. 73 Copyright 2023, Wiley. (D) Sequential targeting of TGF-β signaling and KRAS mutations for improved therapeutic efficacy in pancreatic cancer.…”
Section: Molecularmentioning
confidence: 99%
See 2 more Smart Citations
“…(C) Schematic depiction of a hydrogel platform for codelivery of CAFs and cancer cell-targeted nanoparticles. 73 Copyright 2023, Wiley. (D) Sequential targeting of TGF-β signaling and KRAS mutations for improved therapeutic efficacy in pancreatic cancer.…”
Section: Molecularmentioning
confidence: 99%
“…For instance, based on the homologous targeting theory, Guo et al employed cell membrane-coated nanoparticles to develop a dual-targeting strategy, wherein nanoparticles were coated with membranes derived from CAFs and tumor cells, respectively. 73 This approach aimed to target CAFs for the delivery of siNNMT to remodel the stroma while simultaneously targeting tumor cells to deliver gemcitabine, thereby synergistically combating drug resistance in pancreatic cancer. To achieve the codelivery of both types of nanoparticles, researchers utilized hydrogels to encapsulate and transport them to the target site via homologous targeting mechanisms, facilitating their therapeutic action (Figure 2C).…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…24−26 By contrast, an alternative strategy of inhibiting the activation of CAFs through antifibrotic drugs, reprogramming them into a quiescent state, is preferable to combat tumors rather than directly kill CAFs. 27,28 Even though, the pre-existing dense ECM still exerts a strong barrier effect on drug and lymphocytic infiltration. Therefore, a comprehensive treatment approach involving both ECM reshaping and CAFs reprogramming is urgently needed to break the physical barrier and strengthen the immunotherapeutic efficiency of fibrotic BRCA.…”
mentioning
confidence: 99%
“…Immunotherapy has emerged as a promising approach to replace traditional postoperative treatments for breast cancer (BRCA). The era of immune checkpoint blockade (ICB) officially commenced with the approval of the first immune checkpoint inhibitor (ICI), Ipilimumab, by the U.S. Food and Drug Administration (FDA) in 2011. However, ICB therapy has not achieved the expected results in clinical treatment of BRCA, mainly due to the adverse tumor-specific microenvironment. On the one hand, BRCA, as a poorly immunogenic cold tumor, makes it difficult for ICIs to effectively block immune escape, failing to the ICB therapy. On the other hand, the unique physiological characteristic of the breast creates an abnormal tumor mechanical microenvironment, where the fibrotic extracellular matrix (ECM) forms a natural physical barrier for drug penetration and immune cell infiltration. Under the tumor microenvironment (TME), abnormally activated fibroblasts, known as cancer-associated fibroblasts (CAFs), are the major contributors to the immunosuppressive formation and also predominant drivers of ECM stiffening. It has been demonstrated that targeting CAFs is conductive to enhance the efficacy of ICIs. , But considering the specific role of CAFs, direct targeting and killing of CAFs seem to be unadvisible, as it would cause the complete breakdown of the tumor matrix to facilitate tumor cell metastasis. By contrast, an alternative strategy of inhibiting the activation of CAFs through antifibrotic drugs, reprogramming them into a quiescent state, is preferable to combat tumors rather than directly kill CAFs. , Even though, the pre-existing dense ECM still exerts a strong barrier effect on drug and lymphocytic infiltration. Therefore, a comprehensive treatment approach involving both ECM reshaping and CAFs reprogramming is urgently needed to break the physical barrier and strengthen the immunotherapeutic efficiency of fibrotic BRCA.…”
mentioning
confidence: 99%